Problems of Sharia Supervisory Board in Sharia Banking - Dahlia, Dea; Mauludiyah, Sri; Anwar, Shahrul; Kania, Dede (Zona Law And Public Administration Indonesia, 2024)
This article aims to discuss the Problems of Sharia Supervisory Board in Islamic Banking, DPS is an independent body in Islamic banking whose main function is to supervise sharia compliance in Islamic banking operations. Within this framework, DPS is an extension of the National Sharia Council (DSN), whose role is to carry out direct and local supervisory functions in Islamic banking, so that the implementation of Islamic banking practices is expected to always run in accordance with sharia values. In this article the author uses a qualitative method, data collection is carried out using literature studies sourced from books and journals that discuss the Problematics of the Sharia Supervisory Board in Islamic Banking. The Sharia Supervisory Board (DPS) plays an important role in ensuring that Islamic businesses, especially Islamic banking, operate according to sharia principles, this role should be expanded as an extension of Bank Indonesia to ensure the development and healthy growth of Islamic banking in Indonesia. This role will be optimal if the DPS operational support tools are available, including legislation and regulations, competent human resources, good management and adequate infrastructure.